Functional assessments for anterior cruciate ligament reconstruction return to sport - Herbst, Elmar; Wierer, Guido; Fischer, Felix; Gföller, Peter; Hoser, Christian; Fink, Christian (Annals of Joint, 2017)
Despite technical advancements in anterior cruciate ligament (ACL) surgery, the high re-rupture and contralateral ACL injury rates following ACL reconstruction remain a clinically and economically relevant problem. ACL re-ruptures are multi-factorial, however premature return to sport and functional deficits are important causes for graft failure and contralateral ACL injuries. While various prevention programs exist, little is known about functional assessment following ACL reconstruction. Most of the functional tests are for research purposes only because of the associated high costs, time and personnel consumption. In order to integrate functional testing into the rehabilitation process and to subsequently improve patient care, test batteries must be clinically applicable. Many tests have been introduced and evaluated, but many of them reflect only limited aspects of the knee and lower limb function. Therefore, test batteries evaluating muscle strength, speed and agility, as well as neuromuscular control have been introduced. In order to properly interpret the test results however, comparison to normative data or longitudinal data are necessary to properly determine the return to sport.